A study of the results related to the effect of FICB with LMA on femoral fracture surgery in primary and middle school children in Iraq (Texas Journal of Medical Science, 2023)
Hip fracture or proximal femur fracture is a very frequent operation in people all over the world. Occupation assumes 20-25% of trauma service beds in the world. It is responsible for disability, loss of quality of life and health, economic and social costs, and has a greater impact than other chronic diseases that afflict our population as different professionals are involved in the care of these patients, so coordination between different levels of care is key to the continuity of care. In addition, more than 85% of hip fractures occur in people over 35 years of age, and the incidence is increasing in the Spanish country; these fractures have increased continuously in the past two decades.